Evaluación de la viabilidad de un tratamiento de aguas por carbón activado obtenido del bambú de la especie Chusquea Scandens Kunth (2021)
For a tertiary water treatment, the viability and effectiveness of the use of activated carbon obtained from bamboo of the Chusquea Scandens Kunth species was evaluated based on its physical-chemical properties, analyzing the percentages of removal of pollutants in the water. The proposal was initially made with a broad search for technical requirements, determining which water pollutants will have the highest affinity and physical adhesion towards organic material. At the end of the diagnosis of the parameters, the characterization of activated carbon was developed to evaluate its adsorptive capacity using the methylene blue technique, moisture content, ash, iodine number, apparent density, pH and finally the adsorption isotherms where it was obtained. a surface area of ​​130.8779 m² / g with N2. Likewise, the water to be treated was characterized with the following analyzes: COD, SST, color, turbidity, conductivity, Hydrocarbons and pH, initially the design of experiments was carried out where the factors considered were the initial concentration of adsorbent and stirring time, the Response variables were the percentages of removal of turbidity and color, obtaining values ​​for these of 71.35% and 56.36% respectively.